Error Performance Analysis of Decode and Forward Based Cooperative Systems with Relay Selection - Akin, A. Ipek; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2013)
In this paper, error performance analysis of a cooperative system with relay selection that utilizes decode and forward (DF) method is considered. The source-relay, relay-destination and source-destination links are modeled as Nakagami-m distributed random variables. The effects of the cooperative maximal ratio combining (C-MRC) used to decrease performance degradation due to error propagation in DF based wireless cooperative networks and classical maximal ratio combining (MRC) methods on error performance of the system are investigated with computer simulations. It has been shown that C-MRC technique provides significant performance improvement with respect to the MRC method.
Keywords: Cooperative communication; decode and forward; relay selection; maximum ratio combining; cooperative maximum ratio combining; Nakagami-m fading; DIVERSITY; NETWORKS; Engineering; Telecommunications